(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Nigerian citizens living outside the country’s borders have always been denied their civil rights to vote and be for. Although diaspora election has become popular in modern democracies around the world, the 1999 Nigerian Constitution and the 2022 Electoral Law made it impossible for the Nigerian diaspora to participate in the electoral process, especially, to vote and be elected, unless they return to Nigeria. This study relied on secondary data to examine the Nigerian diaspora’s aspirations for inclusion in the Nigerian electoral process. The study stated that the right to vote in the diaspora is a universal human right, but denied the Nigerian diaspora. It also found that there are approximately 17 million Nigerians in the diaspora who are constitutionally barred from participating in the electoral process of their home country from outside the country. The study, therefore, recommended amending Nigerian legal instruments to remove residency criteria for participation in the electoral process. This enfranchises the Nigerian diaspora and ensures their inclusion and participation in the electoral process. Again, the Independent National Electoral Commission should set up a voting unit in every Nigerian embassy and commission to facilitate diaspora voting in general elections. This should be preceded by the introduction of the electronic voting system so that the results can be easily transmitted. It was also recommended that the Nigerian diaspora should intensify their mobilization and advocacy towards the National Assembly and the Presidency to achieve the goal of inclusion in the Nigerian electoral process.